An Overview of Gadget Usage Behavior among Elementary Students: A Case Study - Adelse Prima Mulya; Ghina Irval Gustav; Witdiawati Witdiawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Currently, adolescents easily access and use gadgets. However, the adolescent phase is a transitional period of cognitive and biological development that affects behavior, including the use of devices and environmental influences including schools. If the use of devices is excessive and unsupervised, it will affect students' physical, mental and social health. Objective to determine the description of device use behavior, the level of device addiction at SDN Sukamentri Village. The approach of this research is a case study of 274 students of State Elementary School 3, 4, 5 Sukamentri from grades 4, 5, and 6. The data collection using the total sample technique with a sample size of 274 students. The questionnaire used to collect data related to device use behavior is the Indonesian version of the Smartphone Addiction Scale-Short Version (SAS-SV) with a reliability test value of Cronbach's Alpha, R = 0.740. The assessment time was carried out from September 30, 2024 to October 01, 2024. This study was analyzed univariately using frequency distribution tables and percentages. The results show that the majority of students are 10 - 11 years old with even gender. Students who use gadgets are 92.70% with a duration of 2 - 3 hours per day (67.15%). The main access is through personal devices (61.68%). The most common function of device use is playing games (42.34%). The prevalence of high-risk device addiction behavior reached 57.66%. The majority of students use devices to play games with a duration of 2 - 3 hours per day, while personal device ownership has the highest results.